FOREWORD - -, Editor-in-Chief (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2014)
Since it was onlined in 2011, Journal of Harmonia has been accessed by thousands of visitors from all over the world. International index institutions, such as the Directory of Open Access Journal (DOAJ), Google Scholar, Mendely, Citeulike, and Worldcat, have been making Harmonia as one of the journals linked there. Likewise, national index institutions, such as the Indonesia Publication Index (IPI/Portal Garuda), Indonesian Scientific Journal Database (ISJD) that make Harmonia a national indexed journal.Based on the facts above, Harmonia needs to adjust while enhancing the quality and quantity to be more tangible to facilitate the readers and the authors of the article. The change of journal subtitle originally named Harmonia: Jurnal Pengetahuan dan Pemikiran Seni to become Harmonia: Journal of Arts Research and Education, with the entire contents of English articles from Volume 14 Number 1 in 2014 is an effort towards the dissemination of the content of Harmonia articles broadly. A manuscript writing guide is adjusted by using one of the standards of writing in the world of publication, namely the American Psychology Association (APA), though it is not entirely adopted. The addition of subtitles âeducationâ in the name of the journal affirms that the scope of the journal focuses on the content of the article about art studies and education.Our great appreciation to all the readers, writers and observers of art and art educators who have been supporting the publication of Harmonia. The expectation is that the presence of Harmonia in a new edition can complete the art literature that can contribute to the development of the science of art and art education.